Species and Density of Gastropods on The Intertidal Zone of The Rocky Shore at Akaiwa, Tomioka, Amakusa, Japan - Karundeng, Joyfullness; Paruntu, Carolus P.; Rumengan, Inneke F. M.; Sinjal, Cathrien A. L.; Kemer, Kurniati; Kaligis, Erly Y. (JURNAL PESISIR DAN LAUT TROPIS, 2026)
Gastropods are a class belonging to the phylum Mollusca, characterised by a single shell and radula. In intertidal ecosystems, they serve as herbivores, detritivores, or predators, and are often used as indicators of environmental health. This study examines the density of gastropods in the rocky shore habitat of Akaiwa, Tomioka Peninsula, Japan. Samples were collected using random quadrats (25x25 cm) in the upper (R1) and lower (R2) intertidal zones. The results show variations in density between zones. In the upper zone (R1), density ranged from 17.60 ind/m² (Japeuthria cingulata) to 52.80 ind/m² (Thais clavigera). Meanwhile, in the lower zone (R2), density ranged from 4.80 ind/m² (Clypeomorus petrosa) to 52.80 ind/m² (Lunella correensis). The species Cellana nigrolineata also showed high density in both zones (R1: 41.60 ind/m²; R2: 54.40 ind/m²). Overall, the density pattern on the rocky shore of Akaiwa indicates variation influenced by vertical zonation, where distinct physical characteristics and environmental pressures in each zone shape the unique distribution of gastropod abundance. Keywords: Akaiwa, density, gastropoda, intertidal zone, rocky shore   Abstrak Gastropoda adalah kelas dalam filum Moluska  yang dicirikan oleh cangkang tunggal dan radula. Dalam ekosistem intertidal, mereka berperan sebagai herbivor, detritivor, atau predator, serta sering menjadi indikator kesehatan lingkungan.  Penelitian ini bertujuan untuk menghitung kepadatan gastropoda di habitat pantai Rocky Akaiwa, Semenanjung Tomioka, Jepang. Sampel diambil menggunakan kuadrat acak (25x25 cm) pada zona intertidal atas (R1) dan bawah (R2). Hasil menunjukkan variasi kepadatan antar zona. Di zona atas (R1), kepadatan berkisar antara 17,60 ind/m² (Japeuthria cingulata) hingga 52,80 ind/m² (Thais clavigera). Sementara di zona bawah (R2), kepadatan berkisar antara 4,80 ind/m² (Clypeomorus petrosa) hingga 52,80 ind/m² (Lunella correensis). Spesies Cellana nigrolineata juga menunjukkan kepadatan tinggi di kedua zona (R1: 41,60 ind/m²; R2: 54,40 ind/m²). Secara umum, pola kepadatan di pantai Rocky Akaiwa menunjukkan variasi yang dipengaruhi oleh zonasi vertikal, dengan karakteristik fisik dan tekanan lingkungan yang berbeda di setiap zona membentuk distribusi kelimpahan gastropoda yang khas. Kata kunci: Akaiwa, kepadatan, gastropoda, pantai rocky, zona intertidal